Wysiłek emocjonalny jako podstawowa zasada miłości (dworskiej). Romans z Anomenem w Baldur’s Gate II - Bednorz, Magdalena (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article undertakes an analysis of the only romantic plot for a female character in Baldur’s Gate II: Shadows of Amn, namely the romance with Anomen, one of the player character’s potential companions. The analysis focuses primarily on how this romance adapts themes of courtly love to the poetics of the digital game medium. Courtly love is treated here not as a realistically depicted medieval tradition but rather as an established pop-cultural reference to the literature of the period, and as an element of contemporary depictions of the Middle Ages, often serving as a way to present contemporary themes and beliefs. The analysis therefore aims to explore how the theme can be employed to reproduce contemporary patterns of romantic relationships within a game, and in the case of Anomen, how it reproduces patterns of unequal emotional labor in heterosexual relationships. The article thus seeks to show how digital games can function as tools of cultural discourse of love by implementing certain patterns of romantic love through their specific means of expression.